Assessing The Usability Of Websites: Standards And Guidelines Versus User Perception - Mousavi, Maryamossadat (2009)
Usability of websites captured attention from many parties as it is an important marketing tool. standards and guidelines are developed to ensure high usability but somehow usability has a culture-nature related which may affect the usability. This study compares the usability of websites as defined b the standard and the Iranian end users as well.